Perception and management of Oestrus ovis human myiasis by physicians: Exploratory survey in an endemic area (Italy) - Fahad Ahmed; Carlo Carta; Daniele Satta; Luca Varcasia; L. Kirsty Pourshahidi; Sebastian Alessandro Mignacca; Lia Cavallo; Antonio Scala; Antonio Varcasia; Claudia Tamponi (PLoS ONE, 2025)
Background Myiasis caused by the sheep nasal botfly is endemic in countries where sheep and goats are largely reared, while humans serve as incidental hosts. Ophthalmomyiasis in humans caused by Oestrus ovis is documented globally but is most prevalent in Mediterranean countries, highlighting the significance of this myiasis as a neglected disease. Method A thorough questionnaire covering frequency of disease occurrence, seasonal patterns, and management of O. ovis was forwarded to clinicians in Italy gathering data from 100 respondents across diverse regional and occupational backgrounds. Results Majority of respondents were from endemic areas of the Southern Italy and main islands, like Sardinia (52%) and Sicily (42%), with 81% representing physicians. Notably, 31% of physicians reported treating ophthalmomyiasis cases, while 80% expressed interest in further information. Seasonal trends revealed a peak during summer (χ² = 29.429, df = 4, p < 0.001), notably among outdoor workers in contact with farm animals (χ ² = 18.059, df = 2, p < 0.001). Diagnosis relied on symptoms or parasite detection, with ocular regions being the most common site of infestation. O. ovis was identified in 13% of cases (χ² = 20.368, df = 3, p < 0.05), with physicians emphasizing the importance of removing larvae painlessly to avoid complications. Finally, physicians reported the efficacy of mercuric oxide ointment and the use of topical povidone-iodine for ocular localization, combined with antibiotics and corticosteroids. Conclusions Diagnostic challenges and the persistence of recurrent infestations highlight the need for enhanced disease surveillance and clinician knowledge to effectively manage and mitigate the impact of ophthalmomyiasis as it continues to emerge as a significant public health concern.